О зимовке личинок слепней в УССР - Бошко, Г.В.; Шевцова, Н.П. (Вестник зоологии, 1975)
Chrysops caecutiens L. larvae hibernate under water at positive temperatures. Tabanaus autumnalis L. hibernate above the water line in soil at the depth from 2-3 to 17-20 cm where soil temperature in winter is not below -4°. The data are given of laboratory experiments on the effect of negative temperatures on the survival rate of T. autumnalis L. larvae.